Influence Of Foreign Uranium On The United States Market - T. A. Boyden (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
The Free World uranium market is now characterized by production nearly twice that of consumption result- ing in a rapid build-up of uranium inventories. Low- cost production from high-grade deposits in Australia and Western Canada will gradually add another 10 to 15 million pounds U308 annually into Free World production throughout the 1980's. This latter material cannot be absorbed in further inventory build-up and can only displace higher cost production. The result is a restructuring of the Free World producer industry. United States and Eastern Canadian producers have the higher cost production which gradually will be displaced from the market during this decade. As United States production declines, United States utilities must increase their reliance on foreign supplies in order to meet their needs. This paper reviews the elements that will cause the restructuring of the Free World producer industry and the expected response of the United States utility industry to that developing situation.